PERENCANAAN WAHANA BERMAIN PROFESI ANAK DENGAN PENEKANAN ARSITEKTUR METAFORA DI KOTA SAMARINDA - Utoyo, Agustina; Efendi, Arman; Mudrajad, Dimas Bintang (LPPM Universitas 17 Agustus 1945 Samarinda, 2020)
Play gives the child an opportunity to develop their emotional, physical, social and logical abilities. Game focus is applied to the characteristic of Samarinda city is the typical food of Samarinda and the culture of village Pampang. Currently there is a profession game but still not equipped with adequate facilities for children. Then done research with the purpose of planning rides playing children's profession with the emphasis of metaphors with the limitation of problems for the perpetrators of children aged 0-5 years The results of the study showed a large space coefficient of building base of 6,410.9795 m2, the size of the green base coefficient of 5,636.606 m2 with the distribution of 78 rooms from 9 mass of buildings. Site location plan is located at Jl. Untung Suropati, District Sungai Kunjang, so planning using the concept of metaphor, where the transformation of rectangular shapes and circles that form Lego and for the building mass that is radial surrounding the building. A metaphor concept that follows the shape of a Lego because the game is often played by children